The ETH Innovation & Entrepreneurship Lab: Supporting Young Entrepreneurs - Tomas Brenner (CHIMIA, 2020)
For the successful launch and sustainable growth of innovative technologies into business concepts, extensive knowledge and a wide variety of tools are needed. The ETH ieLab provides exactly the right framework and support for this.